2005
DOI: 10.1186/1743-8454-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the subarachnoid space and lymphatics: Is it time to embrace a new concept of cerebrospinal fluid absorption?

Abstract: In most tissues and organs, the lymphatic circulation is responsible for the removal of interstitial protein and fluid but the parenchyma of the brain and spinal cord is devoid of lymphatic vessels. On the other hand, the literature is filled with qualitative and quantitative evidence supporting a lymphatic function in cerebrospinal fluid (CSF) absorption. The experimental data seems to warrant a re-examination of CSF dynamics and consideration of a new conceptual foundation on which to base our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
159
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 88 publications
12
159
0
2
Order By: Relevance
“…Also, in monkeys, lymphatic vessels have been observed in spinal epidural tissues [126]. Since there is no direct evidence supporting direct spinal CSF-BISFlymph connections so far, it appears that CSF-BISF from the spinal subarachnoid compartment first passes into the epidural tissues from which absorption takes place into blind ending lymphatic vessels ( [116] Figures 1E-1F). Quantitatively, studies employing sheep model showed that the relative proportion of CSF absorption by the spinal compartment amounts to about 25% of total CSF-BISF clearance [127].…”
Section: Endeavor To Understand Pathways For Lymphatic Drainage Of Csmentioning
confidence: 99%
“…Also, in monkeys, lymphatic vessels have been observed in spinal epidural tissues [126]. Since there is no direct evidence supporting direct spinal CSF-BISFlymph connections so far, it appears that CSF-BISF from the spinal subarachnoid compartment first passes into the epidural tissues from which absorption takes place into blind ending lymphatic vessels ( [116] Figures 1E-1F). Quantitatively, studies employing sheep model showed that the relative proportion of CSF absorption by the spinal compartment amounts to about 25% of total CSF-BISF clearance [127].…”
Section: Endeavor To Understand Pathways For Lymphatic Drainage Of Csmentioning
confidence: 99%
“…CSF drainage occurs directly into the blood via arachnoid villi or granulations into the venous sinuses of the dura mater and also into the lymphatic system via cranial and spinal nerves [138]. Drainage occurs along the olfactory nerves to the nasal mucosa to the cervical lymph nodes [16,17,59,101,172,188] and along spinal nerves to cervical, intercostal, and other lymph nodes [103]. An additional pathway for CSF/ISF drainage appears to occur within dural lymphatic vessels to the cervical lymph nodes [7,113], but just how CSF enters the dural lymphatic vessels has not been well described.…”
Section: Csf and Isf Compartmentalization And Drainage Pathwaysmentioning
confidence: 99%
“…5), no CSF flow from the foramen of Monro to the lateral ventricles was detected. The lack of CSF flow at the level of the aqueduct, and clinical symptoms by increased intracranial pressure support the existence of additional flow paths 19,20 . The contrasting characteristics of CSF flow in the lateral ventricles of these patients suggest that time-SLIP CSF imaging can be used to characterize the pathophysiology of CSF dynamics.…”
Section: Discussionmentioning
confidence: 99%